1997
DOI: 10.1182/blood.v90.10.4078
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Mutation in P53, p53 Expression, Cytogenetics, Histologic Type, and Survival in Patients With B-Cell Non-Hodgkin's Lymphoma

Abstract: In the biology of a cell, the central role of p53 in controlling functions such as G1/S transition (check point) and DNA damage repair, and as a trigger of apoptosis, is well established. Somatic mutations or other changes in P53 have been reported in numerous tumor types, and in some of these, they are associated with poor prognosis. In this study, we examined 237 cytogenetically characterized B-cell non-Hodgkin's lymphomas (B-NHLs) for somatic changes in P53 by Southern blot analysis, by single-strand confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 64 publications
5
54
0
1
Order By: Relevance
“…The p53 tumor suppressor gene is affected in a wide range of human cancers, including hematological malignancies [5][6][7][8][9][10]. In some lymphoid tumors, p53 mutations have been associated with a poor prognosis and with disease progression [11][12][13][14][15][16]. The p53 gene encodes a nuclear phosphoprotein, p53, which plays a key role in cell cycle arrest, induction of apoptosis, and DNA damage repair [17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p53 tumor suppressor gene is affected in a wide range of human cancers, including hematological malignancies [5][6][7][8][9][10]. In some lymphoid tumors, p53 mutations have been associated with a poor prognosis and with disease progression [11][12][13][14][15][16]. The p53 gene encodes a nuclear phosphoprotein, p53, which plays a key role in cell cycle arrest, induction of apoptosis, and DNA damage repair [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that, at the time of diagnosis, 20% B-NHL have somatic mutations in the p53 gene and expression of p53 is remarkably higher among mutated p53, espe-cially when a missense mutation is identified [16]. However, 50% of those with wild type p53 also have a high p53 expression detected by immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…18 Moreover, it has been shown that NHL patients with p53 mutation also have significantly shorter overall and progressionfree survival time. 18,47 In veterinary medicine, Dhaliwal et al 34 evaluated the expression of P53 using immunohistochemistry in 31 dogs with lymphoma. They reported 7 dogs (22%) to be positive for P53 expression and the expression of P53 was statistically correlated with survival.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to occur regularly in nodal lymphomas with the highest incidence in diffuse large B-cell lymphomas. Certain mutations and p53 expression were associated with a poor survival in distinct subtypes of lymphomas (12). Groenbaeck et al (19), having applied PCR, investigated mis-sense and loss-of-function mutations in the p53 gene also in a small group of diffuse large B-cell lymphomas of the skin (REAL classification) and cutaneous MALT-type lymphomas and found no clear-cut correlation with expression of p53, which was present in 2 ⁄ 6 cases of the former type.…”
Section: Discussionmentioning
confidence: 99%